TSUNAMI EVACUATION BEHAVIOR ANALYSIS - Thai CHARNKOL (IATSS Research, 2006)
Evacuation behavior analysis is known to be one step in a transportation disaster response. The purpose of this study was therefore, to investigate permanent and transient resident's behaviors and their backgrounds during a hypothetical tsunami evacuation. Evacuation behavior data were collected from two affected areas, Phuket and Phang-nga, Thailand. A behavioral analysis was carried out to gain some insights into human responses to a future tsunami warning, especially in determining evacuees' response patterns (fast, medium, and slow) under various conditions (four preparation and response time intervals, i.e., 60 minutes, 45 minutes, 30 minutes, and 15 minutes). Preparation and response curves, which represent the time at which the evacuees were expected to begin their evacuation and move to a safer area, were estimated and compared between the permanent and transient residents. Furthermore, evacuation models were employed using binary logistic regression techniques to estimate the likelihood of evacuees being involved in each response group (quick or slow group). Results of the models revealed natural reactions to tsunami evacuation warning, including the response times and evacuation behaviors based on their different backgrounds. This research could help address and improve future evacuation management to become more efficient and more effective, which can increase public safety for the community.